DINAMIKA MODEL EPIDEMIK SVIRS TERHADAP PENYEBARAN PENYAKIT INFLUENZA DENGAN STRATEGI VAKSINASI KONTINU - -, SALMAH; Marentek, Tonaas K.W.Y.; Afri, Lusi Eka (Universitas Pasir Pengaraian, 2015)
The research about dinamica model epidemic SVIRS by continous vaccination strategy in sread of influenza used mathematical models. The result gots free of disease equilibrium (